Eye movements during change detection: the role of depth of field. Issue 2 (19th June 2019) - Zhang, Tingting; Xia, Ling; Liu, Xiaofeng; Wu, Xiaoli
Abstract : This study investigates the eye movements when detecting changes in the scene with different levels of depth of field. A within‐subjects experiment was conducted using a flicker paradigm to create change blindness phenomenon. This experiment investigated two main factors: depth of field and position. The eye‐tracker Tobii X120 was used to record participants' eye movements when looking for changes in the flickering scenes. It was concluded that a small depth of field could indeed direct viewers' attention into the sharp area. The size of the depth of field could not influence the amount of time for change detection whereas uniform blur could facilitate change detection.